A System Architecture for Live Immersive 3D-Media Transcoding Over 5G Networks - Doumanoglou, Alexandros; Zioulis, Nikolaos; Griffin, David; Serrano, Javier; Phan, Truong Khoa; Jimenez, David; Zarpalas, Dimitrios; Alvarez, Federico; Rio, Miguel; Daras, Petros (2018 IEEE International Symposium on Broadband Multimedia Systems and Broadcasting (BMSB), 2018)
The upcoming 5G networks, among other technological advances, bring Network Function Virtualization (NFV) capabilities enabling deployment of application service intelligence on their Next Generation Core (NGC). Application specific logic is packaged into Virtual Network Functions (VNFs) so that their instantiation and deployment can be done at any node of the NGC, with their management and orchestration being maintained by the 5G infrastructure. While the number of instances of each VNF and their placement inside the NGC network are managed by the 5G infrastructure, such management cannot be optimal without application context. In this paper, we propose a 5G oriented system architecture for a next generation augmented virtuality tele-immersive two-player video game application. In the presented video game, the players compete in a capture the flag race in an innovative game movement control setting which uses motion capture technology to allow the players to interact with the game via their body posture and hand gestures. On the top of this, real-time 3D-Reconstruction technology is utilized to create 3D avatars of the players and embed them inside the game environment. Apart from the players, the application also supports real-time spectating of the game action by a considerable amount of spectators that join the live game via client software designed for desktop PCs, smartphones and tablets, connected through mobile or fixed access networks. To distribute the 3D traffic to such a number of consumers that have different device capabilities and are located at varying geographical locations while offering the highest possible Quality of Experience (QoE), is a challenging task. One of the contemporary ways to address this problem is via adaptive streaming. To realize this concept, realtime 3D-Media Transcoders need to be employed. The proposed system architecture considers packaging the aforementioned 3D-Media Transcoders as VNFs that can be deployed on 5G infrastructure. In the paper, it is shown that such an architecture can decrease costs for a given level of offered QoE, with evident benefits for the game service's shareholders. While the application type presented in this paper is fixed, the proposed system architecture can be adopted by other applications of similar context with similar benefits gained from the flexible deployment of virtualised applications in 5G networks.